Normatividad procesal aplicable en el arbitraje internacional - Zappalá, Francesco (2023)
The theory of the autonomy of the will of the parties has received wide recognition in national legal systems. With good faith, legality, and respect of international due process as the only requirements, the agreements and regulations on international commercial arbitration clearly establish that the parties can choose t he applicable procedural law. The present regulatory situation in various states can be presented as two possibilities. In the first possibility, the contracting parties select the seat of international arbitration from within a legal system that adopts th e criterion of geographical location. In the second possibility, the parties choose the seat of arbitration from within a legal system that adopts the view of the autonomy of the will of the parties. This paper purports to demonstrate the prevalence of con tractual intent over the so -called lex arbitri at the transnational level.